Gingival fibroblast seeded bioengineered scaffolds for treatment of localized gingival recession - Rajul Chordia; Aritri Ghosh; Shalini Dasgupta; Sayandeep Saha; Tirthankar Debnath; Ashit Kumar Pal; Ananya Barui (Biomedical Engineering Advances)
Gingival recession is a prevalent issue present in most of the Indian population, associated with interproximal tissue deficiency, leading to dental problems. Its treatment has remained a major problem in the field of periodontics due to autologous graft morbidity and limited healing associated with the current artificial grafts. The present study aims to is to develop bio-engineered chitosan-gelatin scaffolds seeded with primary gingival fibroblasts to address gingival recession as noninvasive grafts. Gingival fibroblasts were seeded on scaffolds with varying chitosan-gelatin ratios (1:1, 1:3) (v/v) and a chitosan control. Comprehensive characterization included morphological, mechanical, biochemical, and cellular analyses including cell viability, migration and transcriptomic studies. The chitosan-gelatin scaffolds (1:3) demonstrated a highly porous architecture with satisfactory biodegradation and swelling capacity. Furthermore, in vitro studies show significantly higher cellular compatibility, fibroblast migration, and F-actin expression. The upregulation of FGF-2 gene in this scaffold indicates its potential for promoting fibroblastic growth and improved wound healing potential. In addition, the antibacterial impact reflect its clinical potential of the fibroblast-seeded chitosan-gelatin (1:3) scaffold for potential tissue engineering applications in periodontal regeneration.